Development of Web Appgeyser Assisted E-learning Media to Improve Students' Critical Thinking Skills on Physics’s Quantities and Units - Siska Desy Fatmaryanti; Sintya Delisa; Ashari Ashari; R. Wakhid Akhdinirwanto (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2022)
This research produces E-learning media assisted by Web Appgeyser using Physics E-module with Quantity and Unit material. The purpose of this study was to determine the feasibility in terms of validity, practicality, and effectiveness of the developed media. This study uses a 4D development model, namely Define, Design, Development and Dissemination. The research was conducted at SMA Negeri 6 Purworejo with the research subject in a limited trial of class X6 totaling 10 students and a broad trial phase totaling 71 students in class X4 class X7. The instruments used in the study were validation sheets, student response questionnaires, implementation of lesson plans, and tests of students' critical thinking skills. Data analysis techniques in this study are validity test, reliability test, and N-gain test. Based on the research results obtained: (1) the results of the validation of learning materials seen from the two validators got an average value of 3.8 in the "very good" category and media experts got an average value of 3.8 with the "very good" category, so it can be said to be valid, (2) the practicality of learning media as seen from the implementation of lesson plans with a percentage agreement of 99% which is included in the "reliable" category and student response questionnaires with a percentage of 82.06% in the "good" category, (3) the effectiveness of learning media as seen from the the increase in learning outcomes of critical thinking skills is 0.78 with the "high" category.